MSMEs and the informal sector: Highlights from SHiFT Work Package 2 - CGIAR (CGIAR, 2024)
The informal sector plays a vital role in food systems in low–and middle–income countries (LMICs). Micro, small, and medium enterprises (MSMEs) encompass a wide range of actors, including food processors, wholesalers, distributors, and retailers.Learn how the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT)is empowering MSMEs and the informal sector to sell more sustainable, nutritious foods in this video featuring Alan de Brauw, SHiFT’s Work Package 2 Lead.